Status of Forests and Conservation Approaches of Tragopan Blythii in Nagaland - Watiao, A. R. (Indian Forester, 1998)
Nagaland is known for its richness in biodiversity. The State also harbours as many as 200 species of epiphytic and terrestrial orchids, many of which are rare and endangered. Under Wildlife Programmes, the conservation of Tragopan blythii, a rare and endangered species found in the Nagaland has been initiated to save this bird from extinction.